CPA Examinations: Accounting Practice. - Chamberlain, John H. (The Accounting Review, 1966)
The article provides several problems prepared by the Board of Examiners of the American Institute of Certified Public Accountants presented as the second half of the certified public accountant examination in accounting practice on May 19, 1966.